Benevolent Childhood Experiences and Depressive Symptoms Among Chinese Undergraduates: A Moderated Mediation Model Examining the Roles of Uncertainty Stress and Family Relationship - Zhang, Caiyi; Wang, Wei; Pei, Yifei; Zhang, Ying; He, Chenlu; Wang, Jingjing; Gao, Xiuyin; Hou, Hao (Frontiers in Public Health, 2021)
Background: The evidence on the association between Benevolent Childhood Experience (BCE) and depressive symptoms in students is complex. This study aims to explore the underlying mediation mechanism of BCE towards depressive symptoms and whether this link was moderated by family relationship among Chinese undergraduates. Methods: From March 2021 to May 2021, a cross-sectional study was conducted in China, and 1821 undergraduates was recruited in this study. Participants were asked to complete a self-reported electronic questionnaire. The software SPSS PROCESS macro was used to tested the mediation and mediated moderated modelling analysis. Results: Mediation analysis indicated that Uncertainty Stress (US) partly mediated the link between BCE and depressive symptoms (indirect effect = -0.47, 95% bootstrap CI =-0.55, -0.39). The indirect effect of US accounted for 39.63% of the total variance in depression. Moderation analysis indicated that the association between US and depressive symptoms was significantly modified by family relationship (interact effect = -0.019, P＜ 0.001). An integrative moderated mediation analysis indicated that the indirect effect from BCE to depressive symptoms through US was also moderated by family relationship (interact effect = -0.012, P = 0.014). Conclusions: US plays a key role in bridging BCE and depressive symptoms while the family relationship can buffer the impact of US on depressive symptoms among Chinese undergraduates. Enhance tolerance of uncertainty and improve family relationship are needed to protect undergraduates from depressive symptoms.